Crystal Growth and Scintillation Properties of Non‐Stoichiometric Cs2LiLaBr6:Ce. Issue 10 (25th August 2019) - Lin, Jia; Wei, Qinhua; Zhang, Di; Tang, Gao; Qin, Laishun; Shi, Hongsheng
Abstract: Because of incongruent melting, phase separation occurs when Cs2 LiLaBr6 :Ce (CLLB:Ce) is grown from a melt using stoichiometric raw materials. In this study, raw materials with different amounts of excess LiBr are used to grow CLLB:Ce crystals. It is found that enough excess of LiBr is beneficial to the crystal growth of CLLB:Ce. A transparent 1 × 2‐in. CLLB:Ce single crystal is successfully grown by the vertical Bridgman method. The differential scanning calorimeter‐thermogravimetric analysis (DSC‐TG), X‐ray diffraction, and inductively coupled plasma mass spectrometry results are used to understand the crystallization behavior at different stages of the crystal growth process. The luminescence and related scintillation properties of the CLLB:Ce single crystal are investigated. The relative light output of the CLLB:Ce single crystal is about 48 000 ph MeV −1, which is 80% that of the LaBr3 :Ce crystal. The energy resolution of the CLLB:Ce single crystal is 4.0% at 137 Cs 662 keV. Abstract : Because of incongruent melting, phase separation occurs when Cs2 LiLaBr6 :Ce is grown from a melt using the stoichiometric raw materials. Additional LiBr suppresses the formation of Cs3 LaBr6 second phase during crystal growth. Transparent 1 × 2‐inch Cs2 LiLaBr6 :Ce single crystal is achieved by the vertical Bridgman method when the excess amount of LiBr reaches to 20 mol%.